Anticoagulation Reversal and Risk of Thromboembolic Events Among Heart Transplant Recipients Bridged with Durable Mechanical Circulatory Support Devices. Issue 7 (September 2019) - Moretz, Jeremy; Lindenfeld, Joann; Shah, Ashish; Wigger, Mark; Schlendorf, Kelly; Keebler, Mary; Danter, Matthew; Brown Sacks, Suzanne; Ooi, Henry; Brinkley, Marshall; Hanna, Peter; Zalawadiya, Sandip
Abstract : Anticoagulation reversal agents (ARAs) can minimize bleeding complications associated with mechanical circulatory support devices (MCSDs) explantation at the time of heart transplantation (HT); data on thromboembolic (TE) risk associated with ARAs are limited in this patient population. In this single-center study, we retrospectively analyzed 118 consecutive adults who were supported with durable MCSDs and underwent HT between May 2013 and October 2016. Patients were categorized based on intraoperative use of ARAs (recombinant factor VIIa [n=23], 4-factor prothrombin complex concentrate [n=48], or factor IX complex [n=2]) at the time of HT; these agents were used at discretion of implanting surgeons for bleeding control. The primary outcome of interest was presence of venous or systemic TE events within 3 months of HT. Multivariable logistic regression analyses were used to assess association between TE events and use of ARAs. A total of 71 (60%) patients received ARAs, and a total of 32 patients (27.1%) had TE events (25 venous [median time to diagnosis: 11.5 days; interquartile range IQR: 9–31 days], and 10 systemic [median time to diagnosis: 5.5 days; IQR: 4–8 days]); 26 (81.2%) of those with TE events had ARAs used at the time of HT. Multivariable analysis identified use of ARAs as an independent predictor of TE events (multivariable odds ratio: 3.06; 95% CI: 1.09–8.58; p = 0.034). Unplanned intraoperative use of ARAs to control bleeding was associated with a significantly higher risk of TE events among HT recipients bridged with durable MCSD. Future studies are required to further assess safety of these agents and their impact on patient outcomes. Abstract : Supplemental Digital Content is available in the text.